Radiative and magnetohydrodynamic micropolar hybrid nanofluid flow over a shrinking sheet with Joule heating and viscous dissipation effects - Ishak, Anuar; Waini, Iskandar; Pop, Loan Mihai (Springer Science and Business Media Deutschland GmbH, 2022)
This study examines the radiative and magnetohydrodynamic micropolar fluid flow over a stretching/shrinking sheet consisting of Al2O3 and Cu nanoparticles. Besides, the effects of the Joule heating and viscous dissipation are taken into consideration. The similarity variables are employed to convert the governing equations into similarity equations. Then, the bvp4c in MATLAB is utilized to obtain the numerical results. The accuracy of the current formulation and method has been done by comparing the present results with those previously published data. Findings discovered that two solutions are obtained for the limited range of S and K, and these solutions are terminated at S ¼ Sc and K ¼ Kc. The influence of Ec and R is to reduce the local Nusselt number of Rex1=2 x Nux. Meanwhile, the values of Rex1=2 x Nux increase with the increase in uhnf when larger values of R are considered. The rise of M contributes to the increment in the values of Re1=2 x Cf , RexMw, and Rex1=2 x Nux, but the effect of K lowers the values of these physical quantities. Lastly, it was discovered that the first solution is physically reliable and in a stable mode.